VISUAL PRESENTATION OF CYBERSPACE: ANALYZING THE PRODUCTION DESIGN OF THE FILM, FREE GUY - Liu Guangquan; Azhari Md Hashim; Norman Yusoff, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
Cyberspace is a virtual world in a computer network. With the continuous development of information technology and the continuous expansion of the boundary of art, more and more artists and designers focus their exploration on the visual presentation of cyberspace. Video games and sci-fi movies have become the testing ground for the visual image of cyberspace. The film Free Guy is a science fiction film based on video games. The film production designers designed a fantasy and colourful cyberspace for Free Guy, which has been widely praised for its visual presentation. Therefore, this study mainly analyzes the visual representation of cyberspace from the production design of the film Free Guy.